Ramona's world - Cleary, Beverly; Tiegreen, Alan (New York : Morrow Junior Books, 1999)
Follows the adventures of nine-year-old Ramona at home with big sister Beezus and baby sister Roberta and at school in Mrs. Meacham's class. (Gr. 3-5)
750
Accelerated Reader AR
Keywords: Schools -- Fiction; Family life -- Fiction